2020
DOI: 10.1037/rev0000223
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation and comparison of models of risky intertemporal choice.

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
1
21
0
1
Order By: Relevance
“…Importantly, we modeled the delay to the larger reward with a transition probability and used the MDP, a utility based model, to compute action values when the transition probabilities were higher than expected (certain environment) and lower than expected (uncertain environment), which made the TD simulations risky intertemporal choices. We found that impulsive agents performed worse when transition probabilities to larger, delayed rewards were higher than expected, similar to previous findings using probabilistic future rewards (for reviews, see [ 61 , 62 ]). However, when the transition probabilities to delayed rewards in the environment were lower than expected, the impulsive agent with the lower discount factor collected more average reward than the non-impulsive agent that chose larger, future rewards that were not delivered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, we modeled the delay to the larger reward with a transition probability and used the MDP, a utility based model, to compute action values when the transition probabilities were higher than expected (certain environment) and lower than expected (uncertain environment), which made the TD simulations risky intertemporal choices. We found that impulsive agents performed worse when transition probabilities to larger, delayed rewards were higher than expected, similar to previous findings using probabilistic future rewards (for reviews, see [ 61 , 62 ]). However, when the transition probabilities to delayed rewards in the environment were lower than expected, the impulsive agent with the lower discount factor collected more average reward than the non-impulsive agent that chose larger, future rewards that were not delivered.…”
Section: Discussionsupporting
confidence: 90%
“…It remains an open debate whether attribute-comparison (i.e. time vs. time and probability vs. probability) or utility based models are more appropriate for capturing intertermporal choice behavior and neural representation, and there are many kinds of intertemporal choices based on combinations of attributes [ 62 ]. Here we demonstrate an example where an impulsive agent can perform better than a non-impulsive agent, and this example could be extended to other kinds of intertemporal choices by using mismatched expectations across a range of attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus on the motivations and processes underlying people’s withdrawal decision permits an opportunity to go beyond these descriptive results and speculate on their potential implications for understanding how and why people arrived at their decision. Multiple studies of the psychology of human judgment and decision-making have proven the difficulties some people have in understanding exponential growth and in overcoming present bias (e.g., Luckman et al, 2020 , McKenzie and Liersch, 2011 , Soll et al, 2013 ;), that combine to make the offer of immediately available large sums of money very tempting ( Argento et al, 2015 , Munnell and Webb, 2022 ). We found that many people made the decision to withdraw almost immediately, and did not, or could not, estimate the impact of the transfer on their longer-term retirement savings.…”
Section: Discussionmentioning
confidence: 99%
“…Equations 25 and 26 encompass the special cases, as well the case where goods are both delayed and probabilistic. The only other successful general model of risky intertemporal choice is the RITCH model (Luckman et al, 2020).…”
Section: Variations On Rachlin's Themesmentioning
confidence: 99%